Production of wheat-Haynaldia villosa Robertsonian chromosomal translocations - Wilson, Jamie Jo (Kansas State University, 2008)
Common, bread, or hexaploid wheat, Triticum aestivum L. (2n=6x=42, AABBDD), has several relatives in the Triticum/Aegilops complex of the Poaceae family in the Triticeae tribe, which are valuable sources for broadening genetic diversity and may provide genes for disease and pest resistance and general wheat improvement. Other wild relatives of wheat also may be exploited for wheat improvement, such as Haynaldia villosa (L.) Schur. (2n=2x=14, VV). It is a diploid species with resistance to powdery mildew, wheat curl mite colonization, cereal eyespot disease, rust diseases, and wheat spindle streak mosaic virus. H. villosa may harbor many other as yet unidentified traits for wheat improvement. The polyploid nature of bread wheat allows tolerance to genomic changes, because homoeologous chromosomes from other genomes compensate for missing wheat chromosomes. In this experiment, we crossed the disomic alien addition line DA4V (2n=6x=44) with a pair of H. villosa chromosomes added to the wheat chromosome complement with wheat monosomic for chromosome 4D (2n=41) to produce 4D/4V double monosomic plants. According to centric breakage-fusion mechanisms, univalents tend to break at their centromeres at meiotic metaphase I producing telocentric chromosomes with unstable or “sticky” ends that can fuse with the sticky ends of other newly formed telocentric chromosomes. This fusion results in Robertsonian whole-arm translocations that may be compensating if a short arm of one chromosome fuses with a long arm of another. Double monosomic plants were screened cytogenetically and further visualized by genomic in situ hybridization (GISH). Five transfers were identified, including T4DS.4VL and T4VS.4DL translocations, and a T4VS-W.W transfer of unknown wheat origin. These results were confirmed by GISH. The T4DS.4VL and T4VS.4DL translocations are genetically compensating and should be exploited in wheat improvement.
Keywords: Robertsonian translocation; Haynaldia villosa; Agriculture, Agronomy (0285); Agriculture, Plant Pathology (0480); Biology, Genetics (0369)